2012
DOI: 10.1139/o11-086
|View full text |Cite
|
Sign up to set email alerts
|

CobB1 deacetylase activity in Streptomyces coelicolor

Abstract: Silent information regulators are NAD(+)-dependent enzymes that display differential specificity toward acetylated substrates. This report provides first evidence for deacetylation activity of CobB1 in Streptomyces coelicolor. The protein is highly conserved in streptomycetes. The CobB1 protein catalytically removes the acetyl group from acetylated bovine serum albumin. In the absence of NAD+ or when NAD+ was substituted with nicotinamide, deacetylation was stopped. We isolated gene encoding AcetylCoA syntheta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…lividans encodes two sirtuin deacetylases, CobB1 and CobB2, and a Zn(II)-dependent AcuC-type deacetylase. Work with the closely related organism Streptomyces coelicolor demonstrated that Acs was acetylated and that CobB1 deacetylated Acs in vitro (190). However, the acetyltransferase responsible for the acetylation of S. coelicolor Acs was not identified.…”
Section: Acs From Streptomyces Lividans Is the Exception To The Acs Amentioning
confidence: 99%
“…lividans encodes two sirtuin deacetylases, CobB1 and CobB2, and a Zn(II)-dependent AcuC-type deacetylase. Work with the closely related organism Streptomyces coelicolor demonstrated that Acs was acetylated and that CobB1 deacetylated Acs in vitro (190). However, the acetyltransferase responsible for the acetylation of S. coelicolor Acs was not identified.…”
Section: Acs From Streptomyces Lividans Is the Exception To The Acs Amentioning
confidence: 99%
“…Around the same time, an investigation of the cobalamin biosynthesis operon in Salmonella led to the discovery of a bacterial sirtuin ortholog, CobB (13), uncovering a bacterial enzyme involved in the regulation of acetylation. CobB was found to regulate acetyl coenzyme A (acetyl-CoA) synthetase (Acs), the second characterized acetylated protein (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). A protein acetyltransferase, Pat, was discovered a few years later in Salmonella (24).…”
mentioning
confidence: 99%
“…The SePat homologue of Streptomyces lividans (SlPatA) has protein acetyltransferase activity that modulates the activity of the acetoacetyl-CoA synthetase enzyme of this bacterium (6). Acetyl-CoA synthetase was also found to be regulated in vivo by acetylation in Streptomyces coelicolor, but the acetyltransferase responsible for this acetylation was not identified (22). The B. subtilis AcuA (211 residues) and Rhodopseudomonas palustris KatA (RpKatA) GNAT enzymes are much smaller than SePat-type acetyltransferases since they contain only the GNAT domain.…”
mentioning
confidence: 99%